PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS KONSUMEN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA BENGKEL BODY & PAINT PT WAHANA SENJAYA JAKARTA - Prawiniko Sugistianto; Heri Ispriyahadi (STIE Muhammadiyah Jakarta, 2021)
Abstract This study investigates the effect of service quality on consumer loyalty at PT Wahana Senjaya Jakarta Body Paint workshop (Indomobil Nissan Datsun Warung Buncit) by using the intervening variable customer satisfaction. The sample used in the study was 100 customers as respondents. The data were obtained by distributing questionnaires to selected respondents, who were then analyzed using the instrument used in the form of a questionnaire to get primary data for the PLS (Partial Least Square) analysis technique. The results showed that the variable service quality positively and significantly affected the consumer loyalty variable (dependent) either directly or indirectly through the variable customer satisfaction (intervening). Likewise, the consumer satisfaction variable also has a positive and significant effect on consumer loyalty. Excellent service quality will increase customer satisfaction, which becomes the driving force for increased consumer loyalty.